ANALYSIS OF GRAPHITE CARBON BLACK SLURRY DERIVED FROM DURIAN (DURIO ZIBETHINUS) SKIN AS A CANDIDATE FOR BIO-BATTERY ANODE MATERIAL - Khairiah Khairiah; Jafri Haryadi (Universitas Islam Negeri Sumatera Utara Medan, 2019)
In this study, activated carbon from durian skin will be used as a candidate for bio-battery anode material. The precipitation method is used with citric acid and ethanol as the precipitation medium. Durian skin is carbonated and sintered with furnace at temperature of 250 – 1250 °C until it turns into graphite carbon black slurry. Samples are characterized by measuring its absorbency, surface area, pore size, and electrical conductivity. The absorbency increases with increasing value of variables (absorption time, sintered temperature, pore size, surface area, and electrical conductivity). The highest absorbency is 780 mg/g is achieved at 1250 °C, pore radius of 200 nm, surface area of 540 m2/g, and electrical conductivity of 437 S/m.Keywords: absorbency, bio-battery, durian skin, graphite carbon black slurry, and pore size.